"Liberation treatment" for chronic cerebrospinal venous insufficiency in multiple sclerosis: the truth will set you free. Issue 1 (21st November 2014) - Tsivgoulis, Georgios; Faissner, Simon; Voumvourakis, Konstantinos; Katsanos, Aristeidis H.; Triantafyllou, Nikos; Grigoriadis, Nikolaos; Gold, Ralf; Krogias, Christos
Abstract Background Chronic cerebrospinal venous insufficiency (CCSVI) has recently been introduced as a chronic state of impaired cerebral or cervical venous drainage that may be causally implicated in multiple sclerosis (MS) pathogenesis. Moreover, percutaneous transluminal angioplasty of extracranial veins termed "Liberation treatment" has been proposed (based on nonrandomized data) as an alternative therapy for MS. Methods A comprehensive literature search was conducted to identify available published, peer‐reviewed, clinical studies evaluating (1) the association of CCSVI with MS, (2) the reproducibility of proposed ultrasound criteria for CCSVI detection (3) the safety and efficacy of "Liberation treatment" in open‐label and randomized‐controlled trial (RCT) settings. Results There is substantial heterogeneity between ultrasound case–control studies investigating the association of CCSVI and MS. The majority of independent investigators failed to reproduce the initially reported high prevalence rates of CCSVI in MS. The prevalence of extracranial venous stenoses evaluated by other neuroimaging modalities (contrast or MR venography) is similarly low in MS patients and healthy individuals. One small RCT failed to document any benefit in MS patients with CCSVI receiving "Liberation treatment", while an exacerbation of disease activity was observed. "Liberation treatment" has been complicated by serious adverse events (SAEs) in open‐label studies (e.g., stroke, internal jugular vein thrombosis, stent migration, hydrocephalus). Conclusion CCSVI appears to be a poorly reproducible and clinically irrelevant sonographic construct. "Liberation treatment" has no proven efficacy, may exacerbate underlying disease activity and has been complicated with SAEs. "Liberation treatment" should stop being offered to MS patients even in the settings of RCTs.